Analyzing the impact of Foreign Direct Investment on Unemployment rate in the case of Kurdistan Region of Iraq - Rostam, Biaban Nwri (Sulaimani Journal for Humanities, 2019)
Foreign Direct Investment (FDI) is on the key factor in the modern globalized world. The significance of FDI lies particularly in long-run investment capital. It has introduced new technologies, provided job opportunities, brought know-how as well as managerial and entrepreneurial culture and enabled an access to global market. The Kurdistan Region, such as other developing regions, has important opportunities for investment owing to its adoption of free economic policy as well as, its relative stability. In addition, there is a series of stimulus measures to attract more foreign investors like the issuance of an investment law includes many economic incentives, customs and tax. The objective of this paper is to exam the effect of Foreign Direct Investment on unemployment rate in Kurdistan Region for the period of (2006-2018). We additionally included the dummy variables for economic crisis and ISIS war. For this aim, Least Square, Unites root, Johansen Co-integration and Granger causality testes are concluded to analysis the data. The result represents that all the series are integrated of order one in level. It reveals that there is short-run relationship between foreign direct investment and unemployment; however both the variable are negatively influenced by economic crisis and ISIS war.
Keywords: FDI; Unemployment rate; Economic growth; ISIS war; VAR method